Guidance relevant to the reporting of health equity in observational research: a scoping review protocol. Issue 5 (19th May 2022) - Rizvi, Anita; Lawson, Daeria O; Young, Taryn; Dewidar, Omar; Nicholls, Stuart; Akl, Elie A; Little, Julian; Magwood, Olivia; Shamseer, Larissa; Ghogomu, Elizabeth; Jull, Janet Elizabeth; Rader, Tamara; et al.
Abstract : Introduction: Health inequities are defined as unfair and avoidable differences in health between groups within a population. Most health research is conducted through observational studies, which are able to offer real-world insights about etiology, healthcare policy/programme effectiveness and the impacts of socioeconomic factors. However, most published reports of observational studies do not address how their findings relate to health equity. Our team seeks to develop equity-relevant reporting guidance as an extension of the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) statement. This scoping review will inform the development of candidate items for the STROBE-Equity extension. We will operationalise equity-seeking populations using the PROGRESS-Plus framework of sociodemographic factors. As part of a parallel stream of the STROBE-Equity project, the relevance of candidate guideline items to Indigenous research will be led by Indigenous coinvestigators on the team. Methods and analysis: We will follow the Joanna Briggs Institute method for conducting scoping reviews. We will evaluate the extent to which the identified guidance supports or refutes our preliminary candidate items for reporting equity in observational studies. These candidate items were developed based on items from equity-reporting guidelines for randomised trials and systematic reviews, developed by members of this team. We will consult with our knowledge users, patients/public partners and Indigenous research steering committee to invite suggestions for relevant guidance documents and interpretation of findings. If the identified guidance suggests the need for additional candidate items, they will be developed through inductive thematic analysis. Ethics and dissemination: We will follow a principled approach that promotes ethical codevelopment with our community partners, based on principles of cultural safety, authentic partnerships, addressing colonial structures in knowledge production and the shared ownership, interpretation, and dissemination of research. All products of this research will be published as open access.